Spotlight on olaparib in the treatment of BRCA-mutated ovarian cancer: design, development and place in therapy - Lorusso D; Tripodi E; Maltese G; Lepori S; Sabatucci I; Bogani G; Raspagliesi F (Dove Medical Press, 2018)
Domenica Lorusso, Elisa Tripodi, Giuseppa Maltese, Stefano Lepori, Ilaria Sabatucci, Giorgio Bogani, Francesco Raspagliesi Gynecologic Oncology Unit, Fondazione IRCCS, Istituto Nazionale dei Tumori, Milan, Italy Abstract: Epithelial ovarian cancer is the sixth most common cancer among women worldwide and the first cause of death among gynecological malignancies. Most of the patients present recurrent disease and unfortunately cannot be cured. The unsatisfactory results obtained with salvage chemotherapy have elicited investigators to search for novel biological agents capable of achieving a better control of the disease. In the setting of homologous recombination deficiency, the DNA errors that occur cannot be accurately repaired, and the treatment with poly(ADP-ribose) polymerase (PARP) inhibition results in definitive cell death in a process called synthetic lethality. As a result of two positive clinical trials, Olaparib was approved in 2014 by U.S. Food and Drug Administration and European Medicines Agency as the first-in-class PARP inhibitor. Olaparib is effective and well tolerated in homologous recombination deficient patients. Several studies with Olaparib have been conducted in the recurrent setting either as maintenance in platinum-responsive patients or as a single agent. Ongoing trials are focused on the use of olaparib as maintenance in the first-line ovarian cancer setting alone or in combination with antiangiogenic agents. Future perspectives will probably investigate the association of olaparib with novel agents as check-point inhibitors and PI3K-AKT inhibitors. The PARP inhibitor era is just at the beginning. Keywords: olaparib, ovarian cancer, PARP inhibitors, homologous recombination deficiency, BRCA mutation